Political Visions of a Global Challenge - Mendes, Thiago de Araújo (Sustainability in Debate, 2010)
GIDDENS, Anthony. A política da mudança climática. Rio de Janeiro: Zahar, 2010. 316p. ISBN: 978-85-378-0261-8. [Traduzido do original: GIDDENS, Anthony. The politics of climate change. Cambridge: Polity Press, 2009]. Tradução de Vera Ribeiro. Revisão técnica: André Piani.